2009
DOI: 10.1111/j.1365-2966.2009.15307.x
|View full text |Cite
|
Sign up to set email alerts
|

Radio planetary nebulae in the Magellanic Clouds

Abstract: We report the extragalactic radio‐continuum detection of 15 planetary nebulae (PNe) in the Magellanic Clouds (MCs) from recent Australia Telescope Compact Array+Parkes mosaic surveys. These detections were supplemented by new and high‐resolution radio, optical and infrared observations which helped to resolve the true nature of the objects. Four of the PNe are located in the Small Magellanic Cloud (SMC) and 11 are located in the Large Magellanic Cloud (LMC). Based on Galactic PNe the expected radio flux densit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 60 publications
4
30
1
Order By: Relevance
“…Also, for six previously detected objects (Payne et al 2008;Filipović et al 2009;Bojičić, Filipović, and Crawford 2010): LIN 45, SMP S11, SMP S17, LIN 321, LIN 339 and SMP S24, we recorded measurement of flux density in at least one additional frequency, confirming the previous detection.…”
Section: Detection Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…Also, for six previously detected objects (Payne et al 2008;Filipović et al 2009;Bojičić, Filipović, and Crawford 2010): LIN 45, SMP S11, SMP S17, LIN 321, LIN 339 and SMP S24, we recorded measurement of flux density in at least one additional frequency, confirming the previous detection.…”
Section: Detection Resultssupporting
confidence: 65%
“…Based on the radio-continuum properties of radio-bright Galactic PNe the expected radio flux densities at the distance of the SMC is up to ∼2.0 mJy at 1.4 GHz. However, Filipović et al (2009) found that two of the radio detected PNe in the SMC have flux densities >4 mJy at 4.8 GHz, several times higher than NGC 7027, the most radio-luminous known Galactic PN. This implied either a very high mass of the PN progenitor or the doubtful PN nature of these objects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cioni et al 2011), and radio observations (eg. Filipovic et al 2009) the astrophysical tools are finally available to understand the effects of mass, temperature and metallicity during the PN formation and evolutionary cycles in each Magellanic Cloud.…”
Section: The Advantages Of Magellanic Cloud Pnementioning
confidence: 99%